2021
DOI: 10.1177/21925682211065389
|View full text |Cite
|
Sign up to set email alerts
|

Coccydynia—The Efficacy of Available Treatment Options: A Systematic Review

Abstract: Study design Systematic Review Objective To evaluate the efficacy of available treatment options for patients with persistent coccydynia through a systematic review. Methods Original peer-reviewed publications on treatment for coccydynia were identified using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines by performing a literature search of relevant databases, from their inception to January 17, 2020, combined with other sources. Data on extracted treatment outcome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Furthermore, the study revealed that coccygectomy is considered the most effective treatment for refractory cases, and it is the most examined surgical treatment option. [11]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the study revealed that coccygectomy is considered the most effective treatment for refractory cases, and it is the most examined surgical treatment option. [11]…”
Section: Discussionmentioning
confidence: 99%
“…[1,4,5] Individuals who have a history of trauma around the coccyx region develop chronic inflammation around the joint due to repetitive trauma causing coccygeal instability. [6][7][8] The rare syndrome is found to be relatively more common in overweight individuals, and women are likelier to get affected [9][10][11][12] and old age is also considered a risk factor. [13] The anatomy and physiology of the coccyx, which consists of 4 or 5 cranial bones attached to the sacrum, are important in understanding the pain resulting from trauma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroid injection, ganglion impar nerve block, radiofrequency ablation, and prolotherapy with dextrose are among the treatment options. [9][10][11][12][13] When other treatments fail, coccygectomy will be considered. 14 Recently, the effect of extracorporeal shock wave therapy (ESWT) on coccydynia has been considered by some authors.…”
Section: Introductionmentioning
confidence: 99%
“…If the patient does not respond to conservative methods, invasive treatment will be started. Steroid injection, ganglion impar nerve block, radiofrequency ablation, and prolotherapy with dextrose are among the treatment options 9–13. When other treatments fail, coccygectomy will be considered 14…”
Section: Introductionmentioning
confidence: 99%